Analisis Penerapan Model Pembelajaran Project Based Learning Pada Pembelajaran Tematik - Afifah Nur Zuhdiyyah; Indah Nurhidayati; Praptiningsih (Universitas Majalengka, 2023)
This research aims to determine: 1) the application of the Project Based Learning (PjBL) Learning Model, 2) the results of the application of the Project Based Learning (PjBL) Model, and 3) the inhibiting factors encountered in the application of the Project Based Learning model in class IV Thematic lessons in MI Al Islam Mranggen, Polokarto subdistrict, Sukoharjo Regency in 2023/2024. The type of research used was descriptive qualitative, the research subjects in this study were fourth grade students of Madrasah Ibtidaiyah Al Islam Mranggen and the data collection techniques used were observation, interviews and documentation. The research results show that: 1) in its application, teachers plan learning by creating a comprehensive Learning Implementation Plan (RPP). 2) the results of implementing PjBL show that project-based learning encourages students to think creatively and act systematically. 3) inhibiting factors in implementing PjBL were also identified, such as the allocation of time required that goes beyond class hours, limited tools and materials, teachers' lack of understanding of the PjBL model, students' unfamiliarity with project-based learning, and difficulties in determining projects that are appropriate to the learning model.